Preparation and determination number of new ZN (II) complexes with a combination of ligands, studying the effect of laser and evaluating their activity on bacterial swabs - Awos Alezi; Zhour Altaee (College of Education for Pure Sciences, 2018)
Acetylacetoneazineoxime AAOH, acetylacetoneazinebis(oxime) AABOH2, benzilsemicarbazone BScH and benzilsemicarbazone-hydrazone BScZH have been prepared using classical, one pot and microwave heating methods followed by the preparation of new zinc(II) complexes with mixed ligands above using classical and microwave heating (Green Chemistry) methods. The resulting complexes have been characterized using elemental analysis by atomic absorption spectroscopy and CHN analysis, relative molecular weight determination cryoscopi-cally, molar conductance measurements, infrared, electronic and 1H NMR spectra. The study suggests that the above ligands form neutral complexes having general formulas [Zn(AH)(BH)(NO3)2] (where AH= AAOH or AABOH2; BH=BScH or BScZH ligands). Accordingly, hexa-coordinated mononuclear complexes have been investigated having distorted octahedral geometries. The effect of laser have been studied on solid ligands and solid zinc(II) complexes, no effect have been observed on all the compounds through the results of melting point and conductivity, this means that most of the compounds are stable and not affected by this kind of radiation. Also the activity of all the complexes have been evaluated on Tonsillitis from males and Females. They were found to be unactive against this pathogens.